If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 5(5x + 1) Reorder the terms: 25 = 5(1 + 5x) 25 = (1 * 5 + 5x * 5) 25 = (5 + 25x) Solving 25 = 5 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 25 + -25x = 5 + 25x + -25x Combine like terms: 25x + -25x = 0 25 + -25x = 5 + 0 25 + -25x = 5 Add '-25' to each side of the equation. 25 + -25 + -25x = 5 + -25 Combine like terms: 25 + -25 = 0 0 + -25x = 5 + -25 -25x = 5 + -25 Combine like terms: 5 + -25 = -20 -25x = -20 Divide each side by '-25'. x = 0.8 Simplifying x = 0.8
| y=-3-2+5 | | -0.848=-0.2(6.5-2) | | 2.7t^2-13t+5=3 | | 2(4x-2)-2x=0.5x-0.5 | | .125y-10=20 | | 2(4x-2)-2x=2x-3 | | 2(4x-2)-2x=1x-1 | | -3(x+2)+5=5(x+5)+5 | | 15=5-(y+8) | | -6-7+2x-8=2x+7x | | 6y+10=8y | | 2y+7x=2 | | 2(4x-2)-1.5x=1.5x-2 | | -20+x=-12 | | x+9.031=0.348 | | .6w-.5w+.4w=4 | | 2.4x^2+4.2x+1.2=0 | | 3000=(15-.50x)(200+8x) | | 2(4x-2)-2x=2x-2 | | 4y+3=7y | | y=-3-4+5 | | 4h-2h+3=2h+2h | | -9x+x^2=-9 | | -7m+3=31 | | 0.3x-0.5(3-x)=1.3 | | -9x+x^2=9 | | 2s+4b=12 | | 436.6+.37Y=Y | | -5(4p+3)-37=4(3p+3) | | 10y=6y+8 | | 4x^3+4x^2+16x=0 | | 5x-3=-9 |